POLIGAMI DAN BATASANNYA DALAM PERSPEKTIF ISLAM - Henny Yusalia (Wardah, 2013)
Polygamy is a concept that is often caused controversy. This becomes crucial because it relates to various aspects of polygamy sensitive. However, in the viewpoint of Islam, polygamy is legally recognized, although it does not specify as a liability. The emergence of polygamy provisions would not be separated from how the decline in the verse. This aspect will be a major influence. Doing polygamy has major provisions is not easy. There are requirements that must be met by the person who will do polygamy. Polygamy is allowed, but must comply with the main provisions, in order to stay on the desired corridor. This relates to the meaning and wisdom of the permissibility of polygamydown to the lowest place.